The impacts of sports facilities on urban development in Malaysia: a case study of the sports facilities provided by Kuala Lumpur City Hall and Bukit Jalil National Sports Complex / Maassoumeh Barghchi - Barghchi, Maassoumeh (2011)
Currently there is tremendous interest in sport in Malaysia, although sport has only been considered as an industry in the last ten years. Sports facilities have improved rapidly, especially after the country hosted the 16 Commonwealth Games in 1998. Internationally, sports facilities are viewed as playing a new role in cities as catalysts for urban development or to regenerate decaying area of the cities. Such a role also provides better justification for public investment, since the provision of sports facilities requires huge amounts of money for construction, ancillary needs and maintenance. The increase in the amount of public money being spent on sports facilities in Malaysia and the proliferation of sports facilities in the country necessitate an investigation into the wider issue of potential benefits related to the development of sports facilities. The aim of this research was to study some existing sports facilities in Malaysia and to examine the physical, economic and social impacts they have had on their surrounding areas. The research began with an overview of the main sports facilities at state level in Malaysia before focusing on selected sports facilities in Kuala Lumpur Federal Territory; namely, the Bukit Jalil National Sports Complex and four selected facilities developed by Kuala Lumpur City Hall, one in each of the four management zones in the city. The study first examined the impacts of sports facilities as perceived by residents in Kuala Lumpur Federal Territory in general, before surveying each of the four case study sites. The National Sports Complex at Bukit Jalil was examined in greater detail, with special attention paid to the various impacts the Complex has had on urban development in the Bukit Jalil area.